Asociación entre horas laboradas diariamente y presencia de síntomas depresivos en médicos residentes de Perú - Alva Díaz, Carlos (2019)
Introduction: Resident physicians who work more hours a day are prone to suffer mental health problems such as depression, a subject that has been little studied. In this regard, the aim of this study was to determine the prevalence of depressive symptoms and to evaluate the association between the number of daily working hours and depressive symptoms in Peruvian residents. Methods: Analytical cross-sectional study that used the database of the National Survey for Resident Physicians-2016, a voluntary survey issued virtually by the National Council of Medical Residency of Peru to physicians who were undertaking their residency in Peru. The presence of depressive symptoms was considered as having obtained a score ≥3 with the Patient Health Questionnaire-2 scale. The number of hours worked each day was collected through a direct question. To assess the association of interest, prevalence ratios (PR) and their 95% confidence intervals (95% CI) were calculated using crude and adjusted Poisson regressions with robust variance. Results: The responses of 953 residents (41.3% women, mean age: 32.5 years) were evaluated, 14.6% of which presented depressive symptoms. In the adjusted analysis, it was found that the prevalence of depressive symptoms increased for each additional hour worked (PR = 1.11; 95% CI, 1.04-1.17).